ELECTROSPUN BIOMATERIALS AND RELATED TECHNOLOGIES - Adhi Anindyajati (Jurnal Teknosains, 2019)
Electrospun Biomaterials and Related Technologies is a multi-contributed book containing review articles from worldwide authors with industry and academic background. This book is aimed to deliver a compiled overview in biomaterials electrospinning, including strategies, relevant technologies, and state-of-the-art research. The editor, Jorge Almodovar, has chemical engineering background with extensive research experiences and focus on engineering of biomimetic materials. The book consists of nine chapters in 282 content pages. Arranged in a concise format, it delivers a comprehensive but not exhaustive reading text. The chapters cover broad range of topics in electrospinning field, including process reproducibility and robustness, fibrous collagen scaffold, cellulose-based biomaterials, biopolymer nanofibres, green electrospinning, electrospun materials for cancer research, nanofibrous nerve conduits, scaffold for retinal tissue engineering, and smart material. These topics are mainly related to biomedical applications, but studies on environmental engineering are also conferred.